The Importance of Learning English at Public Senior High School in Bali - Ni Putu Andini Desiyanti Laksmi; I Nyoman Bawa Bagiada (Pusat riset dan Inovasi Nasional, 2025)
The COVID-19 pandemic triggered a major transformation in the education system, bringing both opportunities and challenges due to the unfamiliar nature of remote learning. This study aims to explore how online English instruction has been implemented in public senior high schools across Bali, particularly by examining its strengths, limitations, potential benefits, and inherent risks. Employing a qualitative research design, the study involved four English teachers from four different public high schools. Data collection methods included literature analysis, in-depth interviews, and classroom observations.. The study found that online English instruction was shaped by the English for Specific Purposes (ESP) approach, with a particular emphasis on content relevant to the tourism and hospitality sectors. A variety of platforms—such as Zoom, WhatsApp, and other digital tools—were employed to deliver instruction. One of the key advantages identified was the flexibility in time and location, which allowed both students and teachers to access learning materials anytime and anywhere. Furthermore, the availability of diverse digital tools enabled teachers to creatively adapt their teaching strategies. Nonetheless, the implementation also encountered significant barriers, including inconsistent internet access and a lack of adequate digital infrastructure. The study also highlighted opportunities arising from increasing student digital literacy and the expanding use of online learning platforms, which fostered more interactive and engaging learning environments. However, several challenges remained, including low awareness among parents and varying levels of digital competence among educators, which affected the overall effectiveness of the program. The findings underscore the urgent need for sustained teacher training and institutional